2012
DOI: 10.1007/s10695-012-9758-2
|View full text |Cite
|
Sign up to set email alerts
|

Identification of MDP (muramyl dipeptide)-binding key domains in NOD2 (nucleotide-binding and oligomerization domain-2) receptor of Labeo rohita

Abstract: In lower eukaryotes-like fish, innate immunity contributed by various pattern recognition receptor (PRR) plays an essential role in protection against diseases. Nucleotide-binding and oligomerization domain (NOD)-2 is a cytoplasmic PRR that recognizes MDP (muramyl dipeptide) of the Gram positive and Gram negative bacteria as ligand and activates signalling to induce innate immunity. Hypothesizing a similar NOD2 signalling pathway of higher eukaryotes, the peripheral blood leucocytes (PBLs) of rohu (Labeo rohit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 72 publications
0
16
0
Order By: Relevance
“…The LRR prediction using SMART, Pfam, and InterProscan indicates five LRR motifs in zNOD2. However, multiple sequence alignment (Figure ) reveals additional four LRR motifs in zNOD2 (Maharana et al ., ). The zRIP2–CARD (471–551 aa) is present on the C‐terminal end of zRIP2, identified as described earlier.…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations
“…The LRR prediction using SMART, Pfam, and InterProscan indicates five LRR motifs in zNOD2. However, multiple sequence alignment (Figure ) reveals additional four LRR motifs in zNOD2 (Maharana et al ., ). The zRIP2–CARD (471–551 aa) is present on the C‐terminal end of zRIP2, identified as described earlier.…”
Section: Resultsmentioning
confidence: 97%
“…The MDP recognition is well characterized in human (Girardin et al ., ; Tanabe et al ., ; Mo et al ., ), but in fish, it is poorly understood. Our recent in silico study provided some crucial insights into the binding modes of MDP with rNOD2–LRR (Maharana et al ., ), which allowed us to define the active site for zNOD2–LRR in the present study. The modeled zNOD2–LRR contains a concave β‐sheet rich region and a convex α‐helical region (Figure ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Teleosts were used in several studies to investigate the structures, signaling pathways, and antipathogen functions of NOD2 and RIG-I [23,24,25,26,27,28,29,30,31,32,33,34,35]. Extensive related studies have been conducted using zebrafish, and the results indicated that Dr NOD2 and Dr RIG-I were highly conserved and similar to their mammalian counterparts [36,37,38].…”
Section: Introductionmentioning
confidence: 99%